2020
DOI: 10.25046/aj050297
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Based for Basic English Learning Assessment with Augmented Reality

Abstract: Nowadays Augmented Reality (AR) is very popular in teaching and learning, especially in leading student to observe learning material targets which supported by online learning resources using mobile device and wireless technology. Because English is a foreign language, most students have problems in learning English. Generally, their problems were related to low motivation, bad study habit and attitude toward learning. Significantly, formative assessment is important in improving student learning achievement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…The data collected by the experiment between pen-andpaper assessment and MARPAS assessment showed that students agreed on the positive effects of AR, cellular services, and confirmed the usefulness of AR technology in learning [18].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The data collected by the experiment between pen-andpaper assessment and MARPAS assessment showed that students agreed on the positive effects of AR, cellular services, and confirmed the usefulness of AR technology in learning [18].…”
Section: Resultsmentioning
confidence: 58%
“…Based on the year the article was published, the results of research on AR-based assessments were published annually. The research subjects were undertaken at the level of education starting from preschool and primary school [15]- [17] to college [18]- [20]. In accordance with Dey [21] stated that AR is now used in various application domains, including Education.…”
Section: Resultsmentioning
confidence: 99%
“…Using AR technology in the foreign language classes in a nonlinguistic university, future physicists, biologists, technologists, builders, physicians, chemists, architects and other specialists have a unique opportunity in the age of breakthrough information technologies to learn professional foreign language vocabulary by viewing and interacting with 3D models of the objects and even changing them, for example, in the automotive industry it is a three-dimensional model of a car, in construction -a three-dimensional model of a building, in medicine -a three-dimensional model of human cells, in chemistry -a three-dimensional model of a chemical element, in physicsa visualization of the equations of mathematical physics, etc. AR imposes the content directly on the camera, usually via a smartphone, tablet, netbook, or headset [4,9,10]. Using the possibilities of AR in the foreign language classes gives a unique opportunity to visually reproduce processes that are difficult or almost impossible to reproduce with the means of the real world and simply make the learning process fascinating and understandable, for example, to make virtual trips using Expeditions and Cardboard.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, AR systems involve embedding computer-generated objects into the surrounding reality, which is the main difference from virtual reality (VR) systems, which involve the use of an artificially created video sequence [8]. Currently used as devices: AR glasses, controllers, headphones, smartphones, tablets [4,9,10]. These devices allow a person to see and hear digital objects.…”
Section: Introductionmentioning
confidence: 99%
“…One study has uncovered findings such as children seem to understand how to use the augmented reality application as soon as they began to interact with the technology [4]. Another research effort found learning English utilizing AR can help students in learning material and motivated students to learn the language [5]. Another study proposes AR mobile applications in the household to educate parents and caregivers of potentially dangerous objects in the home that may endanger infants [6].…”
Section: Introductionmentioning
confidence: 99%